Translation Quality Assessment of Health Services Based on House’s TQA Model for Foreigners at Pong Phrabat Hot Spring, Chiang Rai Province - Toopmongkol, Worapon; Kasetsukthavorn, Suriya; Chanboon, Somyos (Fa Nuea Journal, 2022)
The objective of this research article was to assess the quality of the source text (ST) translations to the target text (TT) translations from infographic media in order to upgrade health services for any foreigners who came for services at Pong Phrabat Hot Spring, Chiang Rai. The texts were translated from Thai into English based on House’s TQA Model. Group sampling used in this study was infographic information on the hot spring service at Pong Phrabat Hot Spring, Chiang Rai Province. The assessment framework consisted of Thai Language transmission to the target language in English with 3 aspects of accuracy, clarity, and naturalness of the target language respectively. The results showed that the quality assessment of translation language in all 3 aspects was high-level with a total average of 3.94 with S.D. of 0.82. When considering each aspect, the researchers also found that the aspect of accuracy was high-level at 4.17 with S.D. of 0.75. The aspect of clarity was at the highest level at 4.00 with S.D. of 0.89 while the aspect of naturalness was found to be high-level at 3.67 with S.D. of 0.82. Under the House’s TQA Model, this model can be effectively applied to these kinds of translations in terms of the pattern of grammatical, linguistic, and idiomatic translations.